Anesthesia in cats with comorbidities: Considerations in patients with heart disease, kidney disease, liver disease, and geriatric patients (Research, Society and Development, 2025)
This study aims, through a literature review, to present and discuss anesthetic considerations in patients with comorbidities such as cardiac, renal, and hepatic diseases, as well as high-risk anesthesia in geriatric cats, elucidating their influence on anesthetic decision-making in order to reduce perioperative complications. Anesthesia in cats with comorbidities poses a significant challenge for veterinarians, as this species is particularly prone to perioperative complications. Evidence indicates that anesthetic-related mortality is higher in felines compared to dogs, especially in patients with cardiac, renal, hepatic diseases or advanced age. Individualized protocols, guided by the American Society of Anesthesiologists (ASA) risk classification and supported by targeted diagnostic tests, are essential to enhance patient safety. Comprehensive cardiac, renal, and hepatic assessments, together with specific considerations for geriatric cats, are crucial for appropriate drug selection and continuous intra- and postoperative monitoring. This narrative review summarizes the main anesthetic considerations in high-risk feline patients, emphasizing the role of thorough pre-anesthetic evaluation, rational drug choice, and vigilant monitoring strategies in minimizing perioperative complications. It was sought to provide veterinarians with practical guidance to support safer and more effective anesthetic management of cats with challenging clinical conditions.